"Tell me the story of home": Afrofuturism, Eric Killmonger, and Black American malaise. Issue 3 (2nd July 2020) - Harris, Felicia L.
ABSTRACT: Marvel's Black Panther (2018) begins with a young N'Jadaka (aka Erik "Killmonger" Stevens) asking his father, Prince N'Jobu, to tell him the story of home. N'Jobu shares the origin story of Wakanda, a fictional African nation that is the most technologically advanced in the world. However, as the film progresses, a more complicated narrative of "home" emerges for N'Jadaka—a character who fluctuates between three identities: N'Jadaka, a Wakandan; Erik Stevens, a U.S. American; and Killmonger, a soldier and Navy SEAL. While multiple consciousness may characterize "home" for many Black U.S. Americans, the integration of a familiar account of the Black U.S. American experience into a fantastical, seemingly Afrofuturist text drives the cinematic storytelling of Black Panther into a compelling future-present. With its grueling attention to detail, Black Panther masters the telling of multiple stories, some imaginary and others not, in one sitting. Viewers are swept into an imagined future anchored by heroism, nationalism, and identity coupled with a gripping re-presentation of Black American malaise that gets at the heart of both Afrofuturistic and Hollywood storytelling traditions.